Nazi Paris : the History of an Occupation, 1940-1944. - Mitchell, Allan, 1933- (Berghahn Books, 2008)
Basing his extensive research into hitherto unexploited archival documentation on both sides of the Rhine, Allan Mitchell has uncovered the inner workings of the German military regime from the Wehrmacht's triumphal entry into Paris in June 1940 to its ignominious withdrawal in August 1944. Although mindful of the French experience and the fundamental issue of collaboration, the author concentrates on the complex problems of occupying a foreign territory after a surprisingly swift conquest. By exploring in detail such topics as the regulation of public comportment, economic policy, forced l.